Pakistan’s Intractable Corruption Provides Terror Groups Agency - Gabbay, Shaul M. (Advances in Social Sciences Research Journal, 2023)
This paper discusses the challenges faced by Pakistan, a country in South Asia, with a focus on corruption as a major contributor to the ongoing instability, particularly in relation to terrorism. Corruption has created conditions that are conducive to terrorism by creating economic and political instability, weakening the rule of law, and undermining the legitimacy of government institutions. Terrorist groups, including the Taliban, TTP, and LeT, exploit public frustration to recruit vulnerable individuals, offer financial incentives, and social services. Corruption has led to a lack of accountability, lack of resources, and a breakdown of trust between the government and the people. Furthermore, corruption has contributed to the high turnover of government leadership in Pakistan. The paper also looks at the historical lack of public trust in Pakistan’s government, marked by military coups, political instability, and economic challenges. The paper concludes that unless the issue of corruption is addressed, Pakistan will continue to face significant challenges that undermine its social, political, and economic landscape.